2017
DOI: 10.26666/rmp.jesr.2017.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:The preparation technique during synthesizing process and heat treatment plays an important role in the properties of the ceramic materials. In this paper, ceramic perovskite-type oxide based on Ba (Ce,Zr)O 3 was prepared by sol-gel method and sintered via two-step sintering (TSS) technique. In the TSS, the sintered pellet was undergoing twice heat treatment. The first temperature profile was set at T 1 = 1400°C and the second temperature were varied at T 2 = 1150°C, 1200°C, 1300°C and 1350°C, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is thought that this is related to the intermediate phases, namely: Ba 2 ZrO 4 , sigma-BaP 2 O 7 , Ba 3 P 2 O 8 and CaZrO 3 , formed between the BHA and BaZrO 3 particulates. As stated in Ref [73], Ba 2 ZrO 4 inhibits the grain growth in BaZrO 3 doped ceramics. Studies on barium-substituted hydroxyapatites (Ba-HAs) [74][75][76] have reported that sigma-BaP 2 O 7 and Ba 3 P 2 O 8 phases contribute to a grain size reduction in the HA matrix material.…”
Section: Resultsmentioning
confidence: 74%
“…It is thought that this is related to the intermediate phases, namely: Ba 2 ZrO 4 , sigma-BaP 2 O 7 , Ba 3 P 2 O 8 and CaZrO 3 , formed between the BHA and BaZrO 3 particulates. As stated in Ref [73], Ba 2 ZrO 4 inhibits the grain growth in BaZrO 3 doped ceramics. Studies on barium-substituted hydroxyapatites (Ba-HAs) [74][75][76] have reported that sigma-BaP 2 O 7 and Ba 3 P 2 O 8 phases contribute to a grain size reduction in the HA matrix material.…”
Section: Resultsmentioning
confidence: 74%